2020
DOI: 10.3390/s20154340
|View full text |Cite
|
Sign up to set email alerts
|

Non-Enzymatic Glucose Sensing Based on Incorporation of Carbon Nanotube into Zn-Co-S Ball-in-Ball Hollow Sphere

Abstract: Zn-Co-S ball-in-ball hollow sphere (BHS) was successfully prepared by solvothermal sulfurization method. An efficient strategy to synthesize Zn-Co-S BHS consisted of multilevel structures by controlling the ionic exchange reaction was applied to obtain great performance electrode material. Carbon nanotubes (CNTs) as a conductive agent were uniformly introduced with Zn-Co-S BHS to form Zn-Co-S BHS/CNTs and expedited the considerable electrocatalytic behavior toward glucose electro-oxidation in alkaline medium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As a result, ZnCo 2 S 4 electrode materials exhibit high sensitivity, wide detection lines, and low detection limits, which also make them excellent sensing materials for the electrocatalytic oxidation of glucose. In addition, we compared ZnCo 2 S 4 with other glucose electrocatalytic oxidation materials, showing the excellent electrochemical properties of the ZnCo 2 S 4 material (table 1) [8,[37][38][39][40][41][42][43] To study the specificity of the sensor for glucose, we selected some common organic and inorganic substances that may cause interference, including NaCl, urea (UA), ascorbic acid (AA), hydrogen peroxide (H 2 O 2 ), and SO 4 2− , the concentration of each interfering sample is 1M, and the time interval is the 50s. The results are shown in figure 6(d), even if the concentration of the interfering sample is dozens of times higher than that of glucose, ZnCo 2 S 4 nanomaterials still have no obvious response to these interfering substances.…”
Section: Comentioning
confidence: 99%
“…As a result, ZnCo 2 S 4 electrode materials exhibit high sensitivity, wide detection lines, and low detection limits, which also make them excellent sensing materials for the electrocatalytic oxidation of glucose. In addition, we compared ZnCo 2 S 4 with other glucose electrocatalytic oxidation materials, showing the excellent electrochemical properties of the ZnCo 2 S 4 material (table 1) [8,[37][38][39][40][41][42][43] To study the specificity of the sensor for glucose, we selected some common organic and inorganic substances that may cause interference, including NaCl, urea (UA), ascorbic acid (AA), hydrogen peroxide (H 2 O 2 ), and SO 4 2− , the concentration of each interfering sample is 1M, and the time interval is the 50s. The results are shown in figure 6(d), even if the concentration of the interfering sample is dozens of times higher than that of glucose, ZnCo 2 S 4 nanomaterials still have no obvious response to these interfering substances.…”
Section: Comentioning
confidence: 99%
“…A Zn–Co–S ball-in-ball hollow sphere (BHS) was obtained via ion exchange and a sulfidation method for highly selective glucose detection with a sensitivity of up to 2734.4 μA mM −1 cm −2 and a wide detection range of 5–100 μM. 19 Ni 2.5 Mo 6 S 6.7 was grown on poly(3,4-ethylenedioxythiophene)–reduced graphene oxide (PEDOT–rGO) hybrid membranes via electrodeposition to obtain Ni 2.5 Mo 6 S 6.7 /PEDOT–rGO with high sensitivities toward glucose (666.67 and 266.10 μA mM −1 cm −2 ) and H 2 O 2 (1273.52 μA mM −1 cm −2 ). 20 However, the multiple electron transfer reactions in the detection process make TMS less reversible, resulting in unsatisfactory stability.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have shown that transition metal sulfide nanomaterials, such as MoS 2 [7], CoS 2 [8], CuS [9], and NiCo 2 S 4 [10], were suitable for preparing electrochemical immunosensors that displayed the superior sensing performance. Such an effect was acknowledged to be partly caused by the lower electronegativity of S, which exhibited remarkable electrochemical performance [11,12]. Considering the attractive properties of graphene, greatly enhanced electrocatalytic sensing can be achieved by integrating graphene with transition metal sulfide nanomaterials.…”
Section: Introductionmentioning
confidence: 99%